Portuguese typical starter soups: does salt reduction affect perception and sensory quality at a university canteen? - Damasceno, Karla Suzanne Florentino da Silva Chaves (2021)
Controlling individuals’ salt intakes from discretionary sources is one of Portugal’s public health priority, to reduce factors risks for cardiometabolic diseases. Starter soups, turnip green (TG), Carrot (C) and Carrot with cabbage (CC), from a Portuguese university canteen, were evaluated by sodium content varying in salt addition, the usual amount of salt (R0); with 25% (R25), and 35% (R35) of salt reduction, respectively. One hundred and seven students participated in the research during lunchtime. Check-all-that-apply (CATA) was applied, as well as the acceptability and saltiness perception. There were no differences (p > 0.05) for acceptability and saltiness perception of TG and CC soups with different amounts of salt, but reduced salt samples of carrot soup were perceived to be saltier and overall more liked compared to its usual recipe. This data suggests that 35% of salt reduction is possible in complex matrices as Portuguese starter soups without a loss of acceptance by consumers